Social capital and coping with economic shocks: an analysis of stunting of South African children - Carter, Michael R.; Maluccio, John A. (Elsevier, 2003)
South African households live in an environment characterized by risks, and many face a significant probability of experiencing economic losses that threaten their daily subsistence. Using household panel data that include directly solicited information on economic shocks and employing household fixed-effects estimation, we explore how well households cope with shocks by examining the effects of shocks on child nutritional status. Unlike in the idealized village community, some households appear unable to insure against risk, particularly when others in their communities simultaneously suffer large losses. Households in communities with more social capital, however, seem better able to weather shocks.